IMPLIKASI PERJANJIAN PERDATA DALAM KEHIDUPAN BERMASYARAKAT DI KOTA SAMARINDA - Shilvia Rahayu Safitri; M Haekal Febrian (JOURNAL OF LAW AND NATION, 2024)
This research aims to analyze the implications of civil agreements in community life in the city of Samarinda. Specifically, this research wants to identify the role of civil agreements in providing legal certainty, supporting economic activities, and maintaining public order and security. In addition, this research also aims to identify the challenges in implementing civil agreements in Samarinda. This research uses a qualitative approach with a case study method. Data collection was carried out through in-depth interviews with parties involved in civil agreements in Samarinda, such as business actors, notaries, and local government representatives. In addition, this research also conducted a documentary study of civil agreement documents and related regulations. The data obtained were analyzed using content analysis and thematic analysis techniques. Content analysis was used to identify patterns and main themes in civil agreement documents. Meanwhile, thematic analysis was used to identify the main themes that emerged from the results of interviews with informants. The results of the study show that civil agreements have significant implications for community life in the city of Samarinda. Civil agreements provide legal certainty for the parties involved, support economic activities through guarantees of certainty for business actors, and play a role in maintaining public order and security. However, the implementation of civil agreements in Samarinda still faces challenges, such as lack of public understanding of civil law, low legal awareness, and other problems such as poverty and economic inequality. To overcome these challenges, efforts are needed to increase public understanding of civil agreements and the importance of complying with applicable legal provisions, as well as the role of local governments in creating a conducive climate for the implementation of civil agreements.